The Influence Of Counseling With Audiovisual Media On The Level Of Knowledge And AttitudeAdolescent Women In Consumption Iron Supplement - Iria Ningsih Busri; Afriwardi Afriwardi; Hudila Rifa Karmia (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Giving iron supplement tablets to young women as a program to prevent and treat anemia has so far not worked as expected. To support this program, appropriate health education is needed. The aim of this research was to determine the effect of counseling using audiovisual media on the level of knowledge and attitudes of young women regarding the consumption of iron supplement tablets at Bahrul Ulum Singingi Junior High School.The research method used was quasi-experimental, and the design used was a non-equivalent control group pretest-posttest design. The research was carried out from November 2022 to July 2023 at Bahrul Ulum Singingi Junior High School with a sample size of 88 people using total sampling techniques. Data analysis was done with the Mann-Whitney test using SPSS with confidence index 95%.The results of the research show that counseling using audiovisual media has an effect on the level of knowledge of young women, with the results of the pretest difference between the experimental and control groups p-value>0.05 (p = 0.531), the posttest difference test p-value<0.05 (p = 0.001), and the difference test increasing the p-value <0.05 (p = 0.000). And counseling using audiovisual media also has an effect on the attitudes of young women, with the results of the pretest difference between the experimental and control groups p-value>0.05 (p = 0.338), the posttest difference test p-value<0.05 (p = 0.000), and the difference test increase in p-value <0.05 (p = 0.000).In conclusion, counseling using audiovisual media influences the level of knowledge and attitudes of young women regarding the consumption of iron supplement tablets. Keywords: Counseling Using Audiovisual Media, Iron Supplement Tablets, Knowledge and Attitudes